Cytological changes induced by clethodim in Pisum sativum plant (Bangladesh Journal of Botany, 2020)
Effects of clethodim treatment on mitotic cells of P. sativum were studied in the present investigation. Pisum sativum seeds are treated with different concentrations of clethodim varying from 0.01, 0.02, 0.03 and 0.04% for 1 and 2 hrs and their effect on seed germination, radicle length, mitotic index and chromosomal anomalies were investigated. The outcomes reveal that treatment of clethodim on P. sativum seeds diminishes seed germination, radicle length, and mitotic index in dose-dependent manner. Also, in clethodim treated seeds which are time and concentration dependent, an escalation in the proportion of abnormal mitotic phases was observed. C-mitosis, fragments, precocious separation, stickiness and bridges were the most frequently observed deviations. The results revealed that frequently used herbicide clethodim has a substantial cytotoxic effect on P. sativum.